Computer-Aided Detection Of Brain Tumors Using Image Processing Techniques - (:unkn) unknown (IEEE, 2015)
Computer-aided detection applications has managed to make significant contributions to medical world in today's technology. In this study, the detection of brain tumors in magnetic resonance images was performed. This study proposes a computer aided detection system that is based on morphological reconstruction and rule based detection of tumors that using the morphological features of the regions of interest. The steps involved in this study are: the pre-processing stage, the segmentation stage, the stage of identification of the region of interest and the stage of detection of tumors. With these methods applied on 497 magnetic resonance image slices of 10 patients, the performance of the computer aided detection system is achieved 84,26% accuracy.
Keywords: CAD system; morphological reconstruction; medical image processing